THE ASSOCIATION OF CORPORATE GOVERNANCE AND TAX COMPLIANCE OF INDONESIA STATE-OWNED ENTERPRISES - Novrys Suhardianto; Risandy Meda Nurjanah (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2021)
This study aims to explore the association of SOE monitoring and corporate governance variables and the tax compliance of Indonesian State-Owned Enterprises (SOEs). The samples of this study are SOEs in 2009-2018 listed on the official website of the Ministry of SOEs that have all required data. The data is analyzed using ordinary least square to test the hypothesis with STATA statistical analysis software. The results show that SOEs that receive PSO (Public Service Obligation) and listed on the stock exchange are more tax compliant compared to others. However, the study found no evidence that the governance structure of SOEs affects tax compliance. The data shows that most SOEs still do not have governance structure that comply the regulations. The findings imply that external monitoring received by PSO recipients and listed SOEs improve SOEs tax compliance. Moreover, the findings also imply that SOEs’ corporate governance structure is only a formality and does not take its functions seriously.